The Effect of Business Process Digitalization, Product Affordability, and Social Value on Customer Loyalty for Social Entrepreneurs in Bandung - Sinulingga, Gairah; Setiadi, Bekti; Soesanto, Dasa Rahardjo (West Science Social and Humanities Studies, 2025)
This study examines the influence of business process digitization, product affordability, and social value on customer loyalty in the context of social entrepreneurship in Bandung, Indonesia. Social entrepreneurs operate not only for profit but also for societal benefit, making customer loyalty crucial for sustaining their dual missions. A quantitative approach was employed, involving 130 respondents who had interacted with social enterprises in Bandung. Data were collected through a structured questionnaire using a 5-point Likert scale and analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) version 3. The results reveal that all three independent variables—business process digitization, product affordability, and social value—have significant and positive effects on customer loyalty. Among them, social value has the strongest influence, indicating that customers are more likely to remain loyal when they perceive their purchases as contributing to a broader social cause. The study concludes that a combination of technological integration, economic inclusiveness, and social mission clarity is essential for fostering customer loyalty in social enterprises.